2014
DOI: 10.4160/9789290604549
|View full text |Cite
|
Sign up to set email alerts
|

Catalogo de variedades de papa nativa con potencial para la seguridad alimentaria y nutricional de Apurímac y Huancavelica

Abstract: A todos los pequeños agricultores, colegas e instituciones que han trabajado de manera conjunta con el proyecto IssAndes en el desarrollo y aplicación de los diferentes conceptos y contenidos en este documento. con potencial para la seguridad alimentaria y nutricional Agradecimiento 4 Catálogo de variedades de papa nativa con potencial para la

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Spooner et al (2005) suggest that the domesticated potato comes from the wild species of the S. brevicaule complex from southern Peru, although this complex extends from Huánuco to Puno. Currently in the region of Cusco, Apurímac and Huancavelica it is common to find conservationist farmers for whom biodiversity is their lifestyle and therefore they grow 50, 100 or 300 varieties of potatoes in plots smaller than one hectare (Fonseca et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spooner et al (2005) suggest that the domesticated potato comes from the wild species of the S. brevicaule complex from southern Peru, although this complex extends from Huánuco to Puno. Currently in the region of Cusco, Apurímac and Huancavelica it is common to find conservationist farmers for whom biodiversity is their lifestyle and therefore they grow 50, 100 or 300 varieties of potatoes in plots smaller than one hectare (Fonseca et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the diversity of Andean tubers is not homogeneous but is identified concentrated in micro-centers of diversity and outside of them less interspecific diversity is conserved: various authors have identified as micro centers of diversification of these: Cajamarca, Huancavelica, Huánuco and Cusco in Perú; in Bolivia the Altiplano and La Candelaria territories; in Ecuador the provinces of Carchi and Huaconas and in Colombia in the departments of Boyacá and Nariño (García & Cadima, 2003;Seminario, 2004;Ortega et al, 2007;Parra-Q. et al 2012;Manrique et al 2014Fonseca et al, 2014). These micro-centers of diversification share a high intravarietal diversity, both morphological and genetic, as well as an important cultural roots of these species.…”
Section: Diversity and Distribution Of Andean Tubers…mentioning
confidence: 99%
“…a) DNA extraction: It was performed using the modified CTAB method (Doyle and Doyle, 1987), for which leaflets were used. The DNA quality and quantity were verified by spectrophotometry using an Eppendorf BioPhotometer, and by electrophoresis on 1 % (w/v) agarose gel.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Peru, the main center of origin of the potato, shows great biodiversity as a result of an Andean culture that has conserved its resources for generations and that nowadays constitutes an important legacy for humanity (Stokstad, 2019). Within this diversity of potatoes, numerous shapes, colors, textures, and flavors have been distinguished and appreciated for centuries by rural families and, currently, also by urban dwellers, which has increased the commercial demand (Fonseca et al, 2014;Tobin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%